Structural Causes and Classification of First Ever Seizures in Adult Patients - Yaseen, Aimen; Khan, Wazir Ali; Shafiq, Faiqa; Ahsan, Hafiz Haseeb; Akhtar, Hamayun; Khan, Mohammad Asad Ullah (Biological and Clinical Sciences Research Journal, 2025)
Seizures represent a common neurological emergency, and identifying the underlying cause of a first seizure episode is crucial for management and prognosis. Brain structural abnormalities are frequently implicated in adults, yet their distribution and association with seizure types remain variable across populations. Objective: To determine the frequency of brain structural causes and types of the first episode of seizures in adult patients. Methodology: This cross-sectional study was conducted in the ER and Neurology departments of Sheikh Zayed Hospital, Rahim Yar Khan, among adult patients presenting with first-onset seizures. A sample size of 280 was calculated, and demographic data, structural causes, and types of seizure were noted. After setting seizure and initial stabilization, all patients underwent an NCCT scan of the brain to determine the structural cause of the seizure. Structural causes were studied, including juxtacortical microvascular disease, neurodegenerative disease, post-stroke, and focal gliosis. When no cause was found after brain imaging and EEG, it was counted under idiopathic etiology, excluding metabolic and infectious causes. Seizures were also classified into focal, generalized, and undetermined seizures. The data were analyzed using SPSS version 26.0. Mean and standard deviations were reported for continuous variables. The chi-square test was used to compare the qualitative variables, with a p-value of less than 0.05 considered statistically significant. The result was as follows: This study comprised 280 subjects. Mean age ± SD of participants was 42.53±16.14 years, comprising 148 males (52.9%) and 132 females (47.1%). Idiopathic cause was found in 28.6%, post-stroke in 20.7%, juxtacortical microvascular disease in 20.4%, neurodegenerative disease in 12.5%, brain tumors in 9.3%, and focal gliosis in 8.6% patients. Generalized seizures were seen in 62.1%, and focal fits in 37.9% patients. Idiopathic causes of seizures were more prevalent in the younger age group (71.25%) from 20-39 years, whereas post-stroke (70.64%) and focal gliosis (41.7%) were more prominent in the elderly group (50-70 years) (p value = 0.00). Neurodegenerative causes of seizures were dominant in females (62.9%), whereas brain tumors, post stroke, and focal gliosis backed seizures dominated males by 61.5%, 67.2% and 66.7% respectively (p value 0.021). Generalized seizures were more common (58%) in patients aged 20 - 39 years, whereas focal seizures included 49.1% patients between 50 and 70 years (p value 0.003). Focal seizures are more prevalent in male patients, at a significant percentage of 60.4% (p value 0.049). Idiopathic and juxtacortical microvascular seizures dominantly showed the generalized type (90% and 73.7%). Focal gliosis (95.8%), post-stroke (75.9%), and brain tumors (61.5%) caused focal seizures. Neurodegenerative diseases showed only the generalized type of seizures (p-value 0.00). Conclusion: First-onset seizures in adults are more common in males than in females. Generalized seizures were seen more than focal seizures. Idiopathic causes were dominant overall; however, post-stroke causes were more prominent in the structural category. Generalized seizures were mainly due to idiopathic, neurodegenerative, and juxtacortical microvascular causes, whereas focal seizures were due to stroke, tumors, and focal gliosis.